The burden of disease and injury in the United States 1996 - Salomon Joshua A; Ezzati Majid; Ebrahim Shahul; Bulzacchelli Maria T; Majmudar Meghna; Tomijima Niels; Begg Stephen; McKenna Matthew T; Michaud Catherine M; Gaber Kreiser Jessica; Hogan Mollie; Murray Christopher JL (BMC, 2006)
Abstract Background Burden of disease studies have been implemented in many countries using the Disability-Adjusted Life Year (DALY) to assess major health problems. Important objectives of the study were to quantify intra-country differentials in health outcomes and to place the United States situation in the international context. Methods We applied methods developed for the Global Burden of Disease (GBD) to data specific to the United States to compute Disability-Adjusted Life Years. Estimates are provided by age and gender for the general population of the United States and for each of the four official race groups: White; Black; American Indian or Alaskan Native; and Asian or Pacific Islander. Several adjustments of GBD methods were made: the inclusion of race; a revised list of causes; and a revised algorithm to allocate cardiovascular disease garbage codes to ischaemic heart disease. We compared the results of this analysis to international estimates published by the World Health Organization for developed and developing regions of the world. Results In the mid-1990s the leading sources of premature death and disability in the United States, as measured by DALYs, were: cardiovascular conditions, breast and lung cancers, depression, osteoarthritis, diabetes mellitus, and alcohol use and abuse. In addition, motor vehicle-related injuries and the HIV epidemic exacted a substantial toll on the health status of the US population, particularly among racial minorities. The major sources of death and disability in these latter populations were more similar to patterns of burden in developing rather than developed countries. Conclusion Estimating DALYs specifically for the United States provides a comprehensive assessment of health problems for this country compared to what is available using mortality data alone.